Om Grundtvigs Sang-Værk I-V - Høirup, Henning (Grundtvig-studier, 1984)
On Grundtvig's Song-Work I-V By Henning HøirupA detailed analysis of the first two volumes of a photographic reproduction of all Grundtvig’s hymns. The twofirst volumes contain the Song-Work for the Danish Church (1837) and Song-Work for the Danish Church-School, which began to appear in 1839 but was not finally finished until 1870. The first volume was first reprinted in Grundtvig’s lifetime and supervised by himself; the second volume was not finished until 1870. Grundtvig’s other hymns and spiritual songs were not published or republished until after his death.Bishop Høirup discusses in detail the various principles that lie behind the first collected edition (I-V, 1868-81) and the edition (I-V, 1944-51) reprinted here. He regrets that the photographic reproduction does not include Volume VI of the second collected edition, which includes variants and notes for all five volumes as well as corrections and indexes. However, this volume is still available on application to the Grundtvig Society’s office at Farvergade 27, 1463 Copenhagen K. Bishop Høirup points out that the reprinted edition fails to take into account important corrections that Grundtvig himself added on the republication of his main work in 1868; it has been the case in this century that the text of the first edition has been preferred to the text authorized by the author himself. In general the reviewer approves this principle, but cites a number of examples to show that the hymns thereby receive a different wording and a different meaning, which occasionally differ from the very first printing and often from the form generally known. This is especially true of The Blessed Day with Joy We See (Den signede Dag med Fryd vi seer) from 1826.The reviewer ends with the hope for a complete edition of all Grundtvig’s writings and considers it natural to begin with the hymns, with a critical apparatus of textual notes, paraphrases and commentaries.